2001
DOI: 10.1046/j.0953-816x.2001.01824.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fear conditioning but enhanced seizure sensitivity in rats given repeated experience of withdrawal from alcohol

Abstract: Repeated experience of withdrawal from chronic alcohol treatment increases sensitivity to seizures. It has been argued by analogy that negative affective consequences of withdrawal also sensitize, but repeated experience of withdrawal from another sedative-hypnotic drug, diazepam, results in amelioration of withdrawal anxiety and aversiveness. We tested whether giving rats repeated experience of withdrawal from alcohol altered their ability to acquire a conditioned emotional response (CER). Male Hooded Lister … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
70
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 42 publications
15
70
1
Order By: Relevance
“…This theory of kindling seizure activity was subsequently supported by several clinical investigations (Booth and Blow 1993;Brown et al 1988;Lechtenberg and Worner 1990, 1991Worner 1996). Work in rats showing that repeated withdrawals from chronic alcohol facilitate inferior collicular kindling afforded critical support for the kindling hypothesis (McCown and Breese 1990), as did other animal studies that demonstrated enhanced seizure susceptibility following repeated withdrawals (Baker and Cannon 1979;Becker and Hale 1993;Becker et al 1997Becker et al , 1998Clemmesen and Hemmingsen 1984;Kokka et al 1993;Maier and Pohorecky 1989;Meert and Huysmans 1994;Ripley et al 2002;Stephens et al 2001;Ulrichsen et al 1995Ulrichsen et al , 1998. This concept of "kindling" of seizure activity following repeated detoxifications has been a major advance, as it provided an appreciation of the necessity of progressive adaptive change preceding withdrawal-induced seizure activity in alcoholics.…”
Section: Concept Of Kindling Seizure Susceptibility With Repeated Witmentioning
confidence: 81%
See 3 more Smart Citations
“…This theory of kindling seizure activity was subsequently supported by several clinical investigations (Booth and Blow 1993;Brown et al 1988;Lechtenberg and Worner 1990, 1991Worner 1996). Work in rats showing that repeated withdrawals from chronic alcohol facilitate inferior collicular kindling afforded critical support for the kindling hypothesis (McCown and Breese 1990), as did other animal studies that demonstrated enhanced seizure susceptibility following repeated withdrawals (Baker and Cannon 1979;Becker and Hale 1993;Becker et al 1997Becker et al , 1998Clemmesen and Hemmingsen 1984;Kokka et al 1993;Maier and Pohorecky 1989;Meert and Huysmans 1994;Ripley et al 2002;Stephens et al 2001;Ulrichsen et al 1995Ulrichsen et al , 1998. This concept of "kindling" of seizure activity following repeated detoxifications has been a major advance, as it provided an appreciation of the necessity of progressive adaptive change preceding withdrawal-induced seizure activity in alcoholics.…”
Section: Concept Of Kindling Seizure Susceptibility With Repeated Witmentioning
confidence: 81%
“…Reports indicate that multiple withdrawals from alcohol impair learning of a conditioned emotional response (CER; Stephens et al 2001;Ripley et al 2003Ripley et al , 2004, a result consistent with a persistent adaptive change. Based on these findings, Stephens et al (2001) argued that altered affective state is not likely to drive relapse.…”
Section: Future Directionsmentioning
confidence: 92%
See 2 more Smart Citations
“…Many of the behavioural changes seen in binge drinkers can be modelled in the rodent (indeed, some of the deficits we have subsequently described in alcoholics were predicted on the basis of our prior rat studies (Stephens et al 2001(Stephens et al , 2005). Thus, the increased propensity to show seizures following several episodes of alcohol withdrawal has been routinely demonstrated (Becker & Veatch 2002).…”
Section: Rodent Model Of Binge Patterns Of Alcohol Intakementioning
confidence: 89%